Subculturing and Gram staining of blood cultures flagged negative by the BACTEC™ FX system: Optimizing the workflow for detection of Cryptococcus neoformans in clinical specimens - Liu, Lingli; Du, Lijun; He, Shuquan; Sun, Tianshu; Kong, Fanrong; Liu, Yali; Xu, Yingchun (Frontiers in Microbiology, 2023)
Objective To investigate whether an incubation time of 5 days (Aerobic/F, Anaerobic/F) and 14 days (Myco/F) blood culture bottles is sufficient to prevent false-negative results. Methods We evaluated 1,244 blood bottles (344 patients) defined as negative by the BACTEC™ FX system. We also reviewed published cases and our own cases of bloodstream infection caused by Cryptococcus neoformans and simulated different scenarios, including different inoculation concentrations, bottle types, and clinical isolates. Results Two bottles (0.16%) were found to contain C. neoformans when subcultured and Gram stained. A 5-day protocol with Aerobic/F bottles was insufficient for the growth of C. neoformans in some cases, and C. neoformans grew better in Myco/F bottles than in Aerobic/F bottles. Conclusion Subculturing and Gram staining after a 5-day protocol were important for the detection of C. neoformans, and Myco/F bottles should be collected for the blood culture of C. neoformans.